A new route to naphthyl ketones via copper-mediated intramolecular aerobic oxidative cyclization of alkynes and sulfonylcrotonates. Issue 106 (1st November 2016) - Wang, Zhi-Qiang; Xu, Kun; Zhang, Xu; Li, Ting; Zheng, Shao-Long; Yu, Lin-Tao; Mao, Wu-Tao; Chen, Chang-Zhong; Wang, Li-Ya
Abstract : A copper-mediated intramolecular aerobic oxidative cyclization of alkynes and sulfonylcrotonates to a variety of highly functionalized naphthyl ketones was developed. Abstract : Herein we report a copper-mediated intramolecular aerobic oxidative cyclization of alkynes and sulfonylcrotonates. This method provides simple, efficient and easy to operate access to a variety of highly functionalized naphthyl ketones with excellent functional group tolerance.